Exploring Tourism Sub-Sector’s Trust in National Tourism Organization: the Case of North Cyprus/TRNC - Jamadi, Maryam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The present research aims to explore the tourism sub-sectors’ (hotels, restaurants and travel agents) trust in national tourism organization (NTO) in north Cyprus. This study applied institutional and cultural theories along with social exchange theory to understand and explore the trust and level of trust of NTO from tourism sub-sectors in the context of their collaboration for the purpose of an efficient performance of tourism system. Trust, especially political trust is significant for successful and effective governance of tourism. There is also a significant relationship between sub-sector’s trust and political support for NTO. For the purpose of this research, a qualitative method has been furnished and data collection accomplished through an in-depth interview with respondents from the sub-sectors. Around 20 respondents participated in this research through face-to-face interview and collected data subjected to the qualitative data analysis stages. All the interviewees were qualified for a purposive sampling approach as they were the managers and owners of the mentioned sub-sectors. Study has also revealed the trust is negatively affected by lack of sub-sector’s influence in the decision making process within the tourism domain. This study has also revealed that sub-sector’s trust in tourism institutions is an adequate predictor of strong support for tourism in general. Limitations and implications of the study, as well as, the suggestion for further research is provided.

ÖZ: Mevcut araştırma, turizm alt sektörlerinin (oteller, restoranlar ve seyahat acenteleri) kuzey Kıbrıs'taki ulusal turizm organizasyonuna (NTO) güvenini araştırmayı amaçlamaktadır. Bu çalışma, kurumsal sistemin kültürel teorilerini ve sosyal değişim teorisini uygulayarak, turizm sisteminin etkin bir performans göstermesi amacıyla NTO'nun turizm alt sektörlerinden aldıkları güven ve güven düzeyini anlamak ve araştırmak amacıyla uyguladı. Güven, özellikle politik güven, turizmin başarılı ve etkili yönetimi için önemlidir. Ayrıca alt sektörün güven ile NTO'ya verdiği siyasi destek arasında da önemli bir ilişki var. Bu araştırmanın amacı doğrultusunda, kalitatif bir yöntem sunulmuş ve alt sektörlerden katılımcılarla derinlemesine görüşme yoluyla veri toplama yapılmıştır. Yüz yüze görüşme yaparak bu araştırmaya yaklaşık 20 kişi katılmış ve nitel veri analizi aşamalarına tabi veriler toplanmıştır. Tüm görüşülen kişiler, söz konusu alt sektörlerin yöneticileri ve sahipleri oldukları için amaçlı bir örnekleme yaklaşımı için kalifiye olmuşlardır. Çalışma, güveni artırabilecek bir ilişki türü için platformun ve olanakların mevcut olmadığını ortaya koydu. Bu çalışma, alt sektörün turizm kurumlarına güveninin, genel olarak turizme yönelik güçlü bir desteğin yeterli bir yordayıcısı olduğunu da ortaya koydu. Çalışmanın sınırlamaları ve sonuçları ile birlikte, daha fazla araştırma önerisi sağlanmıştır.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Prof. Dr. Habib Alipour
Keywords: Tourism Faculty; Trust, tourism institutions, tourism sub-sectors, support for tourism; Tourism--Cyprus (Turkish Republic of Northern Cyprus, 1983-)